IMPLEMENTING STEM PROJECT TO IMPROVE STUDENTS’ CREATIVITY AND LEARNING OUTCOMES IN THE CONCEPT OF CIRCULATORY SYSTEM - Mom, Putheary; Mom, Sreylin; Phann, Sokmean; Srieng, Kimsron; Kong, Sam Ol (Science Education, Institut Agama Islam Negeri Ponorogo, 2024)
STEM education is a learning approach that integrates sciences, technology, engineering and mathematics, and it’s an important tool that successfully educates students from a variety of national and cultural backgrounds for improving students’ learning activities and learning outcomes. The aims of this research are 1) to investigate the effectiveness of STEM project to improve students’ creativity and 2) to examine the effectiveness of STEM project to enhance students’ learning outcomes in the concept of circulatory system. The quantitive research was used for this research, and the data was analyzed by using SPSS. The participants of this study were students 8th grade in biology subject in concept of circulatory system. The 36 students were divided randomly into two group. It was found that student groups’ product on the average value obtained 77.77% which was categorized as a good creativity level. Moreover, according to the students’ post-test result on circulatory system, there was a significant difference between the control group and the experiment group. Thus, the students of STEM project obtained learning outcomes higher than Traditional method. In conclusion, the STEM project has a positive effect to enhance students’ creativity and learning outcomes.